Effects of training on 10 min cycling time trial performance and pacing strategy - Martin, D. T.; Barnes, C.; Bartram, J.; West, N.; Stephens, J.; Michaels, S.; Abbiss, C.; Halson, S. L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In sport, the distribution of work over a defined exercise period has been defined as a "pacing strategy." Both teleoanticipation and feedback mechanisms have been suggested to influence pacing (Abbiss and Laursen, 2008). The purpose of this study was to examine the influence of a 3-wk training camp on the pacing of cyclists that improved overall cycling time trial performance (i.e. responders) in order to gain insight into the role teleoanticipation and feedback mechanisms may play in pacing. Methods: Male competitive cyclists (n=13; 19.9±1.3y, 71.8±5.7kg, maximal aerobic power; 370±36W) completed structured training for 5wks. Cyclists trained for 2-8 hours daily and the program included cycle ergometer sessions 3 d.wk-1. Each week participants performed a 10min cycling Time Trial (TT; Wattbike) at the end an interval session. Power was recorded at 1Hz and maximum mean power (MMP10min) was calculated. Responders were defined as cyclists that improved MMP10min 5-15% from baseline with baseline tests within 5%. The Typical Error (TE) was used to estimate reliability. A priori planned contrasts (paired t-tests) were used to compare MMP10min performance and pacing during baseline and best performances. Pacing was quantified by dividing the 10min time trial into 4, 150s segments. Results: The TE for MMP10min was 1.4%. The best MMP10min produced in the camp was 8.4±2.9% (mean±90% CI) greater than baseline (362±41W vs 334±37W). The perception of effort and post TT heart rate were similar for baseline and best TT performances (~98%max and ~180- 185bpm). On average, the distribution of work for each 150s of the TT10min at baseline and best performance was similar (25%, 25%, 24%, 26%). Following training, the increase in power for each of the four segments (150s) of the TT was 7±3%; 7±2%; 9±2% and 12±3%. Discussion Cyclists selected for this analysis produced a large and consistent increase in MMP10min (~8%) during a 3wk training study. The pacing during baseline testing and best 10min TT were similar. The dramatic increase in cycling power (~7%) during the first 150s of the 10min TT, following training supports the concept of teleoanticipation as feedback mechanisms are less likely to be involved. The improvement in power during the final 150s (~12%) with similar peak heart rates and perception of effort, indicates that peripheral feedback mechanisms may be involved in training improvements. Our data support the concept that both feed forward and feedback mechanisms contribute to training induced improvements in time trial performance.